2020
DOI: 10.3892/or.2020.7467
|View full text |Cite
|
Sign up to set email alerts
|

Long non‑coding RNA GAS5 increases the radiosensitivity of A549 cells through interaction with the miR‑21/PTEN/Akt axis

Abstract: Radioresistance hinders the therapeutic outcomes of radiotherapy in non-small cell lung cancer (NSCLC). Although long non-coding RNAs (lncRNAs) have been demonstrated to participate in the regulation of multiple cell behaviors, whether they can modulate the radiosensitivity of NSCLC and the underlying molecular mechanisms have not been well investigated. In the present study, it was revealed that NSCLC NCI-H460 cells were more sensitive to ionizing radiation (IR) than A549 cells. Using the RNA-Seq method, four… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 45 publications
(48 reference statements)
1
23
0
Order By: Relevance
“…Several reports have also identified the connection between GAS5 and miRNAs. A recent report showed that GAS5 probably indirectly regulates miR-21, whereas its over-expression suppresses miR-21 expression and, hence, increases radiosensitivity of lung tumor cells [ 92 ]. Recently, it was also shown that miR-29-3p antagonizes GAS5 for binding PTEN [ 59 ].…”
Section: The Special Case Of Gas5 and Mirnasmentioning
confidence: 99%
“…Several reports have also identified the connection between GAS5 and miRNAs. A recent report showed that GAS5 probably indirectly regulates miR-21, whereas its over-expression suppresses miR-21 expression and, hence, increases radiosensitivity of lung tumor cells [ 92 ]. Recently, it was also shown that miR-29-3p antagonizes GAS5 for binding PTEN [ 59 ].…”
Section: The Special Case Of Gas5 and Mirnasmentioning
confidence: 99%
“…Researches have also discovered that lncRNAs transcripts were changed because of ultraviolet rays or ionizing radiation in peripheral blood mononuclear cell (PBMC) [28], thymocyte [29] and melanocyte [30]. LncRNA gas5 was discovered in various cancers to play a regulator in radiotherapy efficacy [31][32][33][34][35]. Therefore, we researched the role of gas5 in GCTO regarding radiation in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…Researches have also discovered that lncRNAs transcripts were changed because of ultraviolet rays or ionizing radiation in peripheral blood mononuclear cell (PBMC) [28], thymocyte [29] and melanocyte [30]. LncRNA gas5 was discovered in various cancers to play a regulatory role in radiotherapy efficacy [31][32][33][34][35]. This explains why the role of gas5 in GCTO regarding radiation in vitro was investigated.…”
Section: Discussionmentioning
confidence: 99%